Multivesicular liposomes for sustained release of bevacizumab in treating laser-induced choroidal neovascularization. (1st January 2018) - Mu, Hongjie; Wang, Yiyun; Chu, Yongchao; Jiang, Ying; Hua, Hongchen; Chu, Liuxiang; Wang, Kaili; Wang, Aiping; Liu, Wanhui; Li, Youxin; Fu, Fenghua; Sun, Kaoxiang
Abstract: Bevacizumab is an anti-vascular endothelial growth factor drug that can be used to treat choroidal neovascularization (CNV). Bevacizumab-loaded multivesicular liposomes (Bev-MVLs) have been designed and developed to increase the intravitreal retention time of bevacizumab and reduce the number of injection times. In this study, Bev-MVLs with high encapsulation efficiency were prepared by double emulsification technique, and antibody activity was determined. The results revealed that 10% of human serum albumin (HSA) could preserve the activity of bevacizumab. In vitro release of Bev-MVLs appeared to be in a more sustained manner, the underlying mechanisms of Bev-MVLs indicated that bevacizumab was released from MVLs through diffusion and erosion. Results of sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) demonstrated that bevacizumab could retain its structural integrity after being released from MVLs in vitro . In vivo imaging was used to evaluate the retention time of antibody in rat eyes, while pharmacokinetic analysis was performed on rabbit eyes. These results indicated that Bev-MVLs exhibited sustained release effects as compared to bevacizumab solution (Bev-S). Bev-MVLs could effectively inhibit the thickness of CNV lesion as compared to Bev-S at 28 days after treatment. Furthermore, these data suggest that Bev-MVLs are biologically feasible to increase the retention time of bevacizumab in vitreous humor. This novel Bev-MVLs may therefore serve as a promising sustained release drug delivery system for the treatment of CNV.